La frontiera dimenticata: la strumentalizzazione dell’Artico nella geostrategia americana - A. Lavorio (Rubbettino, 2021)
Historically, the US Arctic has experienced regular ups and downs in its geostrategic valorization, switching from heavy militarization to general disinterest. This article argues that such an alternation can be explained by considering that in US grand strategy the Arctic has been generally considered a means (and not a goal) so that the continental north has assumed different meanings according to the context the US pictured at the global level – at least from the age of polar exploration to the worsening of climate change effects.